Animal health community experience and its implications on public health (Revista Venezolana de Salud Pública, 2018)
We present the results of a project which included five activities in different sectors of the city of Barquisimeto in Lara state, with the intention of determining the level of knowledge that the community has on zoonoses. The activities were made in the communities of Yacural in Santa Rosa parish in two opportunities, in Patarata of Cathedral parish twice and Rotario District in Juan de Villegas parish, all of them in the municipality Iribarren of Lara state. The activities attended a total of 341 people whom were provided information on zoonotic diseases associated with pet ownership emphasizing on measures that can be used for prevention; also 215 pets were attended providing medical care and veterinary diagnostic for ecto and endoparasites; in some pet was found the presence of Rhipicephalus sanguineus, Ctenocephalides sp., Ancylostoma sp., Toxocara sp., Dipylidium caninum, Trichuris sp., Giardia sp. and Ehrlichia sp.
Keywords: Communities; zoonotic diseases; prevention; care